HIV TESTING AND COUNSELLING AMONG THE YOUTH OF GHANA: THE CASE OF TARKWA-NSUAEM AND FANTEAKWA DISTRICT - ANDOH-ROBERTSON, THEOPHILUS (Advances in Social Sciences Research Journal, 2018)
ABSTRACT This study was conducted to examine the factors that contribute to the utilization of HIV Testing and Counselling (HTC) among the youth in Ghana focusing on Fanteakwa District and Tarkwa-Nsuaem Municipality in light of the Health Belief Model. The study involved 424 youths between the ages of 15 - 24. The quantitative approach was used in the study. Multi-stage sampling technique was adopted for the study involving the purposive sampling which was used to select the two districts and then the simple random sampling method which was also used to select the communities and participants. A structured questionnaire made up of 30 items was administered to the respondents to collect data and processed using STATA 15. The results showed that majority of the respondents (over 80%) had heard about HTC and also knew where to go for HIV testing. Again, It was also revealed from the study that as little as 25% had ever taken HIV test at the time of the study with the males being in majority than the females. In addition, more than half of the respondents (57.6%) have been given pre-counselling service before the test and majority of them (67.3%) went back for their test results. It was also found that sex (p = -0.52854), place of residence (p = - 0.67824) of respondents and perceived susceptibility (p = -0.07187) were significantly associated with HTC participation. It was recommended that social media should be used as a tool for disseminating information on HTC and also, the development and mass distribution of Self-test kits for HIV for the youth. Keywords: HIV Testing and Counselling (HTC), Confidentiality, Persons Living with HIV and AIDS (PLWHA), Health Belief Model (HBM).